Assessing OATP1B1- and OATP1B3-mediated drug-drug interaction potential of vemurafenib using R-value and physiologically based pharmacokinetic models - Kayesh, Ruhul (J Pharm Sci, 2020)
Organic anion transporting polypeptides (OATP) 1B1 and OATP1B3 are important determinants of transporter-mediated drug-drug interactions (DDIs). Current studies assessed the OATP1B1 and OATP1B3-mediated DDI potential of vemurafenib, a kinase inhibitor drug with high protein binding and low aqueous solubility, using R-value and physiologically based pharmacokinetic (PBPK) models. The total half-maximal inhibitory concentration (IC(50,total)) values of vemurafenib against OATP1B1 and OATP1B3 were determined in 100% human plasma in transporter-overexpressing human embryonic kidney 293 stable cell lines. The unbound fraction of vemurafenib in human plasma before (f(u,plasma)) and after addition into the uptake assay plate (f(u,plasma,inc)) were determined by rapid equilibrium dialysis. There was no statistically significant difference between f(u,plasma) and f(u,plasma,inc). Vemurafenib IC(50,total) values against OATP1B1 and OATP1B3 are 175 ± 82 and 231 ± 26 μM, respectively. The R-values [R = 1 + f(u,plasma) × I(in,max)/(f(u,plasma,inc) × IC(50,total))] were then simplified as R=1+I(in,max)/IC(50,total), and were 1.76 and 1.57 for OATP1B1 and OATP1B3, respectively. The simulated pravastatin AUC ratio was 1.28 when a single dose of pravastatin (40 mg) was co-administered with vemurafenib (960 mg, twice daily) at steady-state, compared to pravastatin alone. Both R-value and PBPK models predict that vemurafenib has the potential to cause OATP1B1- and OATP1B3-mediated DDIs.